Role and key species of freshwater snails in enhancing plant growth performance of duckweeds (Spirodela polyrhiza) in rice paddy fields - Yudistira, Dwi Harya; Gunawan, Fariz Ardiansyah; Arif, Shahla Aurelia; Sato, Satoru (Kultivasi, 2025)
Freshwater snails are widely distributed in the rice field ecosystem. Freshwater snails’ feeding and metabolic activities can potentially increase the complexity of freshwater ecosystems, particularly through the nutrient cycle. Cipangopaludina chinensis, Physa acuta, and Semisulcospira libertina are commonly found in Japan's paddy field ecosystems. Spirodela polyrhiza is expected to support biodiversity, improve soil fertility, and reduce greenhouse gas emissions in paddy field ecosystems, while providing food and shelter for the snails.  In this study, we investigated the effects of these three snail species on the growth of Spirodela polyrhiza. The results showed that the presence of P. acuta or C. chinensis could promote the growth of S. polyrhiza compared with the presence of S. libertina, a mix, and the control. The relative growth rate for S. polyrhiza in the presence of P. acuta, C. chinensis + P. acuta, and C. chinesis was 1.10 ± 0.39, 1.10 ± 0.39, and 1.06 ± 0.31 fronds/day, respectively. In the S. libertina treatment, the number of S. polyrhiza fronds decreased as the snails consumed the plants. The number of fronds on the last day of treatment was 1.10 ± 1.10 fronds with a relative growth rate of 0.004 ± 0.030 fronds/day, whereas for the combination of C. chinensis + S. polyrhiza it was 4.80 ± 3.32 and 8.70 ± 3.61 fronds, respectively, with relative growth rate 0.13 ± 0.05 and 0.275 ± 0.06 fronds/day, respectively. Interestingly, these interspecific interactions increased S. polyrhiza performance, as indicated by greater frond length, root length, and frond chlorophyll content. This study highlights that interspecific interactions create complexity in the paddy field ecosystem, providing good conditions for biodiversity and indirectly supporting rice production.